COVID-19 IMPACT ON INFORMATION ORGANIZATION: DELIVERING INFORMATION AND LIBRARY SERVICES DURING A PANDEMIC [PRESENTATION] - Moyo, Lesley (Nazarbayev University Library, 2021)
The COVID-19 pandemic has had a profound and far-reaching impact on how we live and work all over the world. The year 2020 and the first part of 2021 were characterized by fear, uncertainty, and rapid change as society took shelter from the menacing pandemic. Yet, during the same time, we witnessed unprecedented transformation as various businesses and enterprises reinvented themselves to combat not only the deadly effects of the pandemic but also the disruption it was causing in all sectors of life. Within higher education, libraries featured prominently among units rethinking their operations in order to effectively support the continuity of research, teaching, and learning in their respective institutions. As a result, creative ways of organizing, accessing, and delivering services and information in spite of the constraints of the pandemic emerged. We saw the birth of curbside services, the enhancement of electronic access to collections, the increase of digitization on demand, and the emphasis on virtual library services such as chat reference and online library classes. This paper is based on the UW-Madison Libraries' experience in planning and delivering services throughout the pandemic and making necessary adjustments as the pandemic circumstances changed. The paper discusses lessons learned and some key insights gained from the planning efforts as well as some of the pitfalls encountered. The paper emphasizes the importance of preparedness and encourages libraries to develop plans for continuity of operations as an integral component of organizing and delivering library services and information. The importance of a strong web presence is highlighted as fundamental to a library’s organization of information as it serves as a portal to library resources and would be the place all of the library patrons would depend on to search for information when the physical library is inaccessible due to an ongoing pandemic or other similar circumstances.
Keywords: Type of access: Open Access; EALC